Effective Teaching strategies in biological education: present and future prospects - Elkhidir, Noreldaim (Open Science Journal, 2020)
Objective: The aim of this study is to explore the diversity of teaching strategies in biological education and expected results on acquisition of knowledge and fulfillment of learning outcomes in an attempt to identify which strategies work best with biology students. Methods: Three databases and search engines were used: Scopus, Google Scholars and Web of Science. Results: The teaching of biological sciences is experiencing evident transformations towards student-centered learning. As educational goals are being modernized in biology at present times. The more computer modelling, simulations and problem-based learning become part of the teaching strategy, the teaching of biology becomes more learner-centered to enhance learners’ critical thinking on complex biological processes.